#TITLE_ALTERNATIVE# - PURNAMA SARI (NIM 151 05 068), DIYAH
Determining the sea boundaries of a State based on the UNCLOS 1982 (territorial sea, contiguous zone, exclusive economic zone and continental shelf) measured from the base line that have been defined in UNCLOS 1982 towards high seas. Withdrawal of the sea boundaries are not included with the reference field used both on the surface of earth, the geoids, ellipsoid, and map projections. Reduction distance from the surface of the earth to the ellipsoid surface using the geodetic formula calculation and results in reduction are used to count on UTM and Mercator map projection system. Reduction distance from the surface of the earth to the ellipsoid surface is not reduced/not significant because the geodetic latitude is zero, so that the surface of the earth coincides with ellipsoid. Reduction in the Mercator projection system for all sea boundaries measurement exceeds the tolerance limit of plotting point accuracy both based on the scale recommended in the TALOS and the scale of Indonesian chart. UTM Projection System, for the territorial sea and the contiguous zone are not significant on the UNCLOS scale and Indonesian scale map. ZEE and continental shelf have significant result toward scale of the TALOS map and the scale of Indonesian chart. Distance reduction results by using geodetic calculation formula on the ellipsoid surface, UTM and Mercator map projection system have different result so that the definition of sea measurement towards reference field is necessary.